Role of carotenoids in light-harvesting processes in an antenna protein from the chromophyte Xanthonema debile - Durchan, Milan; Tichý, Josef; Litvín, Radek; Šlouf, Václav; Gardian, Zdenko; Hříbek, Petr; Vácha, František; Polívka, Tomáš (The journal of physical chemistry. B, 2012)
Chromophytes are an important group of microorganisms that contribute significantly to the carbon cycle on Earth. Their photosynthetic capacity depends on efficiency of the light-harvesting system that differs in pigment composition from that of green plants and other groups of algae. Here we employ femtosecond transient absorption spectroscopy to study energy transfer pathways in the main light-harvesting complex of Xanthonema debile, denoted XLH, which contains four carotenoids--diadinoxanthin, heteroxanthin, diatoxanthin, and vaucheriaxanthin--and Chl-a. Overall carotenoid-to-chlorophyll energy transfer efficiency is about 60%, but energy transfer pathways are excitation wavelength dependent. Energy transfer from the carotenoid S(2) state is active after excitation at both 490 nm (maximum of carotenoid absorption) and 510 nm (red edge of carotenoid absorption), but this channel is significantly more efficient after 510 nm excitation. Concerning the energy transfer pathway from the S(1) state, XLH contains two groups of carotenoids: those that have the S(1) route active (~25%) and those having the S(1) pathway silent. For a fraction of carotenoids that transfer energy via the S(1) channel, energy transfer is observed after both excitation wavelengths, though energy transfer times are different, yielding 3.4 ps (490 nm excitation) and 1.5 ps (510 nm excitation). This corresponds to efficiencies of the S(1) channel of ~85% that is rather unusual for a donor-acceptor pair consisting of a noncarbonyl carotenoid and Chl-a. Moreover, major carotenoids in XLH, diadinoxanthin and diatoxanthin, have their S(1) energies in solution lower than the energy of the acceptor state, Q(y) state of Chl-a. Thus, binding of these carotenoids to XLH must tune their S(1) energy to allow for efficient energy transfer. Besides the light-harvesting function, carotenoids in XLH also have photoprotective role; they quench Chl-a triplets via triplet-triplet energy transfer from Chl-a to carotenoid.
Keywords: Chlorophyta; Energy Transfer; Chlorophyll; chlorofyl; Light-Harvesting Protein Complexes; Xanthophylls; světlosběrné proteinové komplexy; Carotenoids; xanthofyly; přenos energie; karotenoidy